Semiotic Analysis of Fore Cofee Advertisement on YouTube - Esterlita Sharon; Endar Rachmawaty Linuwih; Eka Fadilah (e-LinguaTera, 2025)
In today’s digital era, advertisements play a vital role not only in promoting products but also in shaping narratives that resonate with consumers. This study examines the semiotic elements embedded in Fore Coffee’s YouTube advertisement, applying Roland Barthes’ semiotic theory to explore how verbal and nonverbal signs communicate meaning. Specifically, the analysis focuses on three layers: denotation (literal meaning), connotation (cultural or emotional meaning), and myth (ideological construction). The research employs a qualitative approach with semiotic analysis as the primary method, drawing data from Fore Coffee’s “Segelas Kopi Wujudkan Harapan” advertisement. The findings reveal that the advertisement communicates more than the consumption of coffee it portrays coffee as a symbol of aspiration, identity, and community. Denotatively, the ad highlights everyday interactions such as delivery services, storytelling, and coffee preparation that reflect politeness, professionalism, and craftsmanship. Connotatively, it evokes deeper associations of comfort, inclusivity, and modern lifestyle, positioning coffee as part of personal and social identity. Nonverbal elements, such as the logo, colors, and capitalized slogans like “NEW COFFEE CULTURE,” further amplify this symbolic value. At the mythological level, four dominant narratives emerge: the myth of hope, where coffee becomes a source of motivation and dreams, the myth of authenticity and quality, emphasizing skilled craftsmanship and locally sourced products, the myth of a modern and inclusive lifestyle, aligning coffee culture with progressive values and creativity; and the myth of local empowerment, showcasing coffee as an ethical choice that supports Indonesian farmers and national pride. Fore Coffee’s advertisement transcends product marketing by constructing an ideological narrative that redefines coffee as a lifestyle symbol. Through signs and symbols, it reinforces cultural values of authenticity, inclusivity, and empowerment. This analysis demonstrates how advertising operates as both a commercial strategy and a cultural text that shapes consumer perception and collective identity.